Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1037/drm0000231
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on sleep and dreams: Study in a Portuguese sample.

Abstract: Research has shown that during the COVID-19 pandemic, there were significant changes in sleep quality and dream activity. An increase in dream and nightmare recall frequency and a predominance of aversive emotional and phantasmatic dream content were recorded. The objective of the study was to analyze the pandemic's socio-occupational, psychological and experiential impact, focusing on sleep quality, dream/nightmare recall, and the emotional content of dreams in a sample of Portugal’s adult resident population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…If previous research during the COVID-19 pandemic suggested sleep and dream monitoring as an essential asset in public mental health, that could assist in the identification of vulnerable/high-risk groups during collective crises (Mota et al, 2020; Scarpelli et al, 2021; Schredl & Bulkeley, 2020; Simões et al, 2023), results from this study indicate that dream content analysis might also play a relevant role in this endeavor. Our results also support the psychoanalytic/psychodynamic conception that understanding the relationship between waking and oneiric mental life is extremely helpful in psychotherapeutic settings (Leuzinger-Bohleber & Fonagy, 2012).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…If previous research during the COVID-19 pandemic suggested sleep and dream monitoring as an essential asset in public mental health, that could assist in the identification of vulnerable/high-risk groups during collective crises (Mota et al, 2020; Scarpelli et al, 2021; Schredl & Bulkeley, 2020; Simões et al, 2023), results from this study indicate that dream content analysis might also play a relevant role in this endeavor. Our results also support the psychoanalytic/psychodynamic conception that understanding the relationship between waking and oneiric mental life is extremely helpful in psychotherapeutic settings (Leuzinger-Bohleber & Fonagy, 2012).…”
Section: Discussionmentioning
confidence: 87%
“…Several studies have reported changes in the frequency and content of dreams and nightmares during the COVID-19 pandemic, including themes related to hygiene, confinement, contamination, illness, and loss of loved ones, which are representative of pandemic fears (Kennedy & Grandner, 2021;Mota et al, 2020). A previous Portuguese study (Simões et al, 2023) corroborated these findings, providing empirical evidence that waking-life experiences significantly influenced dream content since those who reported more significant concern about the pandemic and those who experienced the death of loved ones were more likely to dream about COVID-19. According to this study, fear, anguish, and sadness were the primary emotions related to COVID-19 dreams.…”
mentioning
confidence: 99%
See 3 more Smart Citations